2022
DOI: 10.1007/s00421-022-05019-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased exogenous but unaltered endogenous carbohydrate oxidation with combined fructose-maltodextrin ingested at 120 g h−1 versus 90 g h−1 at different ratios

Abstract: Purpose This study aimed to investigate whether carbohydrate ingestion during 3 h long endurance exercise in highly trained cyclists at a rate of 120 g h−1 in 0.8:1 ratio between fructose and glucose-based carbohydrates would result in higher exogenous and lower endogenous carbohydrate oxidation rates as compared to ingestion of 90 g h−1 in 1:2 ratio, which is the currently recommended approach for exercise of this duration. Methods Eleven male participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Therefore, continuous CHO supplementation is recommended during prolonged exercise at moderate-to-high intensities to maintain stable blood sugar levels and CHO oxidation (Stellingwerff and Cox 2014 ; Thomas et al 2016 ). Currently elite endurance athletes generally consume higher amounts of CHO during competitions (i.e., 90–120 g h −1 of multiple transportable CHO) compared to previous practices (Podlogar et al 2022 ; Podlogar and Wallis 2022 ). Another way to conserve CHO sources during prolonged exercise would be a shift towards a greater reliance on fat as a fuel source, since the utilization of CHO is inversely related to the oxidation of fatty acids. Consequently, possessing the ability to effectively utilize fat as an energy source alongside a high CHO intake could enhance durability during prolonged intermittent exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, continuous CHO supplementation is recommended during prolonged exercise at moderate-to-high intensities to maintain stable blood sugar levels and CHO oxidation (Stellingwerff and Cox 2014 ; Thomas et al 2016 ). Currently elite endurance athletes generally consume higher amounts of CHO during competitions (i.e., 90–120 g h −1 of multiple transportable CHO) compared to previous practices (Podlogar et al 2022 ; Podlogar and Wallis 2022 ). Another way to conserve CHO sources during prolonged exercise would be a shift towards a greater reliance on fat as a fuel source, since the utilization of CHO is inversely related to the oxidation of fatty acids. Consequently, possessing the ability to effectively utilize fat as an energy source alongside a high CHO intake could enhance durability during prolonged intermittent exercise.…”
Section: Introductionmentioning
confidence: 99%
“…123 Over the past year, a total of 18 studies have been published using IR/elemental approaches in SES. These studies varied across the investigation of carbohydrate (CHO) utilization/oxidation, 20,113,[124][125][126][127][128] pro-tein synthesis/turnover, 50,64,[129][130][131][132] mineral absorption/status, [133][134][135] energy expenditure, 136 and environmental exposure. this study as the first occasion in which exogenous CHO oxidation has been assessed using IRMS techniques across different feeding strategies.…”
Section: Isotope Ratio and Elemental Msmentioning
confidence: 99%
“… 123 Over the past year, a total of 18 studies have been published using IR/elemental approaches in SES. These studies varied across the investigation of carbohydrate (CHO) utilization/oxidation, 20 , 113 , 124 , 125 , 126 , 127 , 128 protein synthesis/turnover, 50 , 64 , 129 , 130 , 131 , 132 mineral absorption/status, 133 , 134 , 135 energy expenditure, 136 and environmental exposure. 137 …”
Section: Analytical Approaches For Ms‐based Investigations In Ses In ...mentioning
confidence: 99%
“…However, there is a relationship between exogenous carbohydrate oxidation rates and ingestion rates, and evidence shows that ingestion rates higher than 90 g•h −1 are feasible and that this results in very high exogenous carbohydrate oxidation rates [66,[76][77][78][79]]. Yet, evidence for recommending such high ingestion rates (i.e., > 90 g•h −1 ) remains inconclusive, as there appears to be no further improvement in performance [80], no sparing of endogenous carbohydrate stores [71] and, in some cases, aggressive carbohydrate feeding during exercise can result in increased muscle glycogen utilization [81,82]. It could be that athletes whose energy turnover rates during exercise are very high and thus have a high glucose flux to muscle due to increased blood flow proportional to absolute exercise intensity [83] could benefit from carbohydrate ingestion rates that are higher than currently recommended, but this requires further evaluation.…”
Section: During Competitionmentioning
confidence: 99%
“…It has been reported that elite cyclists can tolerate more than 90 g·h −1 of carbohydrates mostly from glucose-based carbohydrates [ 70 ]. We have recently shown higher exogenous carbohydrate oxidation during prolonged endurance exercise in highly trained athletes with carbohydrate ingestion at 120 g·h −1 as compared to 90 g·h −1 [ 71 ]. However, endogenous carbohydrate oxidation was not further spared by the higher carbohydrate dose, and thus whether there would be an additional performance benefit requires clarification.…”
Section: Importance Of Carbohydrates For Competition and High-intensi...mentioning
confidence: 99%